Who gets to define flourishing? Disentangling social science from theology in flourishing measurement and policy prescriptions - Sarah S. Willen; Abigail Fisher Williamson; Colleen C. Walsh (SSM - Mental Health)
In this essay, we advance a conversation initiated on these pages by the recent special issue on “Flourishing and Health in Critical Perspective: An Invitation to Interdisciplinary Dialogue” (Willen, 2022; Willen, Williamson, and Walsh 2022), followed by a response from VanderWeele and the Human Flourishing Program team (VanderWeele et al., 2023). We were pleased to learn of their agreement with several of the concerns we raised — among them the need for more qualitative inquiry into flourishing; greater attention to sociocultural differences; and additional consideration of the impact of structural conditions, power dynamics, and legacies of injustice on opportunities to flourish. Yet significant disagreements persist. In this rejoinder, we clarify a foundational concern that precipitated our initial call for critical dialogue: the entanglement of normative religious values and empirical methods in HFP’s work. This concern becomes even more evident in VanderWeele and colleagues’ published response and more recent work. This essay highlights the normative theological commitments that inform HFP’s measures and findings, and it foregrounds the risks of introducing theological views into the design and conduct of social scientific research. If religious commitments shape concept formulation and measurement, then those commitments will inevitably influence the findings and policy recommendations that result. Researchers, policymakers, public health professionals, and others interested in engaging with HFP’s instruments, findings, and recommendations need to be aware of the context of their emergence as well as the normative assumptions upon which they rest.